The Current Status of Irrigated Agriculture in Cape Verde and Its Link to Water Scarcity - Erik Sequeira; Pedro Leão de Sousa; Augusto Manuel Correia; João Rolim (Agronomy)
In arid regions with low precipitation, like most of the Cape Verde islands, irrigation is essential for maintaining agricultural production and food security. However, due to significant investment needs, it is critical to improve irrigation efficiency and reduce water losses. The aim of this study is to evaluate irrigated agriculture in Cape Verde and its relationship with water scarcity through the calculation of key indicators and the analysis of statistical and remote sensing data. Crop production data were collected from the Ministry of Agriculture and Environment, and climatic data from the National Institute of Meteorology and Geophysics of Cape Verde (INMG) and FAO’s WaPOR platform. The aridity index was calculated using the UNEP method based on data from INMG. The island of Sal showed the lowest aridity index value (0.07), while Cachaço (São Nicolau island) had the highest (0.41). Sugarcane is currently the dominant irrigated crop, covering over 3000 hectares, about 62% of irrigated land, despite its high water demands. The expansion of sugarcane threatens long-term water sustainability and food production. Promoting crops with higher water productivity and technical training are key actions to ensure the sustainability of irrigated agriculture in Cape Verde. Findings point to the urgent need to improve irrigation infrastructure, maintenance, and system design.